The Influence of Organizational Citizenship Behavior, Organizational Commitment, and Organizational Culture on Production Employee Performance with Job Satisfaction as an Intervening Variable: (Case Study at PT. Casuarina Harnessindo Pemalang) - Rengga Kusuma Putra; Tri Handayani; Ulil Inayah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is entitled